Phase Transition Driven Zn-Ion Battery With Laser-Processed V2C/V2O5 Electrodes for Wearable Temperature Monitoring - Deshmukh, Sujit; Vaghasiya, Jayraj V; Michalička, Jan; Langer, Rostislav; Otyepka, Michal; Pumera, Martin (Small (Weinheim an der Bergstrasse, Germany), 2025)
Flexible power supply devices present significant potential for wearable bioelectronics within the Internet of Things. Aqueous zinc-ion batteries have emerged as a viable and safe alternative for power supply in flexible electronics. Nevertheless, typical battery behaviors are generally detrimental with unfavorable phase transition of electrodes, which invariably lead to rapid performance degradation. Here, extraordinary capacity enhancement of 150% is presented, sustained over 60 000 cycles, attained using vanadium carbide MXene (V2C)/vanadium pentoxide (V2O5) heterostructure as cathode. The unique cathode material is created through the rational engineering of MAX (V2AlC), employing a single-step laser writing process. The ultrastable Zn ion battery stands in stark contrast to all previously reported counterparts, which typically exhibit capacity degradation within a few hundred/thousand cycles. The primary mechanisms driving this enhancement include the delamination of V2C MXene and an unexpected favorable phase transition during cycling. Additionally, a wearable power supply is constructed using a series configuration and is integrated with a commercial temperature sensor for wireless, real-time body temperature monitoring. This study highlights the critical role of electrode design for advanced wearable bioelectronics.
Keywords: vanadium carbide; cyclic stability; wearable bioelectronics; aqueous zinc ion battery; vanadium oxide; temperature sensor